Vitamin D and airway infections: a European perspective - Zittermann, Armin; März, Winfried (European journal of medical research, 2016)
Vitamin D has immuno-modulatory properties, and deficient levels of circulating 25-hydroxyvitamin D (<30 nmol/l) may contribute to increased risk of infectious illnesses. This narrative review summarises data on vitamin D status in Europe and updates results of randomised controlled trials (RCTs) regarding vitamin D and airway infections such as tuberculosis (TB) and acute upper respiratory tract infection. In Europe, the prevalence of vitamin D deficiency is up to 37 % in the general population and up to 80 % in nursing home residents and non-European immigrants. Half of TB patients have a migration background. While results of RCTs do not support the concept of beneficial adjunctive effects of vitamin D supplements in anti-TB treatment [odds ratio (OR) = 0.86; 95 % CI 0.62-1.19], the few published RCTs on the prophylaxis of TB suggest some protective vitamin D effects in individuals with deficient circulating 25-hydroxyvitamin D levels. Regarding acute respiratory tract infection, RCTs indicate a significant risk reduction by vitamin D supplements [OR = 0.65; 95 % confidence interval (CI) 0.50-0.85]. There is evidence that daily administration is more effective than high-dose bolus administration [OR = 0.48 (95 % CI 0.30-0.77) vs. OR = 0.87 (95 % CI 0.67-1.14)] and that individuals with deficient or insufficient (30-50 nmol/l) circulating 25-hydroxyvitamin D levels benefit most. Several vitamin D effects on innate immunity may explain these protective effects. In summary, there is possible evidence from RCTs for protective vitamin D effects on TB and likely evidence for protective effects on acute airway infection. Since vitamin D deficiency is prevalent in Europe, especially in institutionalised individuals and non-European immigrants, daily oral vitamin D intake, e.g. 1000 international units, is an inexpensive measure to ensure adequate vitamin D status in individuals at risk.